Geological and glaciological controls of 21,700 active methane seeps in the northern Norwegian Barents sea - Serov, Pavel; Andreassen, Karin; Winsborrow, Monica; Mattingsdal, Rune; Patton, Henry (Frontiers in Earth Science, 2024)
Due to tectonic uplift in the Cenozoic and numerous shelf-wide glaciations during the Quaternary, ~1-2.5 km of sedimentary overburden has been eroded from the Barents Sea shelf, leading to the exhumation and partial uncapping of hydrocarbon accumulations. Widespread natural gas and oil leakage from the glacially eroded middle-upper Triassic reservoir directly into the water column has been documented at the Sentralbanken high in the northern Norwegian Barents Sea. However, it remains unclear whether the hydrocarbon leakage occurs only from the middle-upper Triassic reservoir units in geological settings exceptionally conducive to hydrocarbon leakage, or if other reservoir formations contributed to the release of hydrocarbons into the water column. It is also not clear whether complete erosion of the caprock is a prerequisite for widespread liberation of natural gas and oil from glacially eroded reservoirs across Arctic continental shelves. Here we analyze multibeam echosounder data covering ~5,000 km 2 and a suite of high-resolution P-cable seismic lines from a range of geological structures across the northern Norwegian Barents Sea. Our analyses reveal that ~21,700 natural gas seeps originate from exhumed, faulted and variably eroded structural highs bearing a range of Mesozoic reservoir formations. All investigated structural highs fuel seabed methane release hotspots with no exception. Evident from observations of seismic anomalies, fluid accumulations are pervasive in the subsurface and likely to continue fuelling seabed gas seepage into the future. We also document that gas seepage through faults piercing overburden, caprocks and reaching potential reservoir levels is pervasive at all investigated structural highs. On the Storbanken high and the Kong Karl platform, such fault-controlled seepage is more prevalent than seepage from reservoir formations subcropping below the seafloor. Using a simple parametrization approach, we estimate that seeps identified within our multibeam data coverage produce a seabed methane flux of 61 x 10 7 mol/yr (9,803 ton/yr), which is one to two orders of magnitude higher than other globally known submarine methane seepage provinces. Fluxes of methane from sea water to the air above the thermogenic gas seep provinces in the northern Norwegian Barents Sea remain to be determined.